1994
DOI: 10.1152/ajpregu.1994.266.3.r756
|View full text |Cite
|
Sign up to set email alerts
|

Control of erythropoiesis in humans during prolonged exposure to the altitude of 6,542 m

Abstract: Altitude hypoxia induces an increase in erythropoiesis. Some of the factors involved in the control of altitude polycythemia were studied. Ten subjects (4 women, 6 men) were exposed for 3 wk to extreme altitude (6,542 m). Blood was withdrawn in normoxia (N) and after 1 wk (H1), 2 wk (H2), or 3 wk (H3) at 6,542 m for the measurement of serum erythropoietin (EPO), blood hemoglobin (Hb), hematocrit (Hct), intraerythrocyte folate (Fol), and plasma ferritin (Fer) concentrations. Renal blood flow (RBF) and absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 0 publications
7
74
1
2
Order By: Relevance
“…Interestingly, both erythropoietin concentrations (Jelkman, 1992;Richalet et al, 1993;Gunga et al, 1996;Levine and Stray-Gundersen, 1997;Chapman et al, 1998), as well as iron turnover (Huff et al, 1951;Reynafarje et al, 1959) return to sea-level values relatively rapidly with chronic altitude exposure. However, the red cell mass continues to increase for up to 8 months of chronic altitude exposure, at least at altitudes above 4000 m (Reynafarje et al, 1959) (Fig.…”
Section: Erythropoietic Effect Of High Altitudementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both erythropoietin concentrations (Jelkman, 1992;Richalet et al, 1993;Gunga et al, 1996;Levine and Stray-Gundersen, 1997;Chapman et al, 1998), as well as iron turnover (Huff et al, 1951;Reynafarje et al, 1959) return to sea-level values relatively rapidly with chronic altitude exposure. However, the red cell mass continues to increase for up to 8 months of chronic altitude exposure, at least at altitudes above 4000 m (Reynafarje et al, 1959) (Fig.…”
Section: Erythropoietic Effect Of High Altitudementioning
confidence: 99%
“…Moreover, despite the apparently normal EPO levels and iron turnover, it is important to point out that this level of stimulated erythropoiesis is elevated for the absolute level of the arterial oxygen content. Thus, when altitude natives, or even altitude sojourners, return to sea level, there is a suppression of erythropoietin (Faura et al, 1969;Jelkman, 1992;Richalet et al, 1993;Gunga et al, 1996;Levine and Stray-Gundersen, 1997;Chapman et al, 1998), a dramatic reduction in iron turnover and bone marrow production of erythroid cell lines (Huff et al, 1951;Reynafarje et al, 1959), and a marked decrease in red cell survival time (Reynafarje et al, 1959). This increase in red cell destruction with suppression of EPO levels has been termed neocytolysis and has been observed under other conditions of a relative increase in oxygen content (Alfrey et al, 1996a(Alfrey et al, , 1996b(Alfrey et al, , 1997Rice and Alfrey, 2000;Rice et al, 2001).…”
Section: Erythropoietic Effect Of High Altitudementioning
confidence: 99%
“…Human studies, for example, have reported no change (Klausen et al, 1991) or even a drop (Richalet et al, 1994) in MCHC with hypoxia-induced increases in blood EPO level. Though plasma osmolality was not recorded in this study, it is possible that changes in this variable may have contributed to the observed differences in MCHC between 'surface swimmers' and 'divers'.…”
Section: Dive Conditioning and Body Oxygen Reservesmentioning
confidence: 99%
“…2 3 During a 3 week sojourn at high altitude (6542 m) the increase in EPO and the subsequent haemoglobin response to EPO were both found to vary considerably. 2 More recently, Ge et al 3 reported a marked individual variability in EPO increase after 6 and 24 h exposure to hypobaric hypoxia equivalent to altitudes of 1780-2800 m. Furthermore, they concluded that altitudes >2100-2500 m might be a threshold for the induction of increased erythropoiesis in most athletes.…”
mentioning
confidence: 98%